Conference review: Barcamp 2020 of the initiative "Media Education Now!" - Swertz, Christian; Pöyskö, Anu; Messner, Sonja (Media Impulses, 2020)
The largest and shortest barcamp of the initiative "Media Education Now!" took place under the motto "Welcome to the Future" on 26.5.20 Online. 80 media educators presented, discussed and reflected on forms of online media work, online youth work and online teaching developed in the face of the Covid crisis in March and April.